The impact of long-term isolation on anxiety, depressive-like and social behavior in aging Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) male rats - Diana I. Mamedova; Olga A. Nedogreeva; Anna O. Manolova; Viktoria O. Ovchinnikova; Pavel A. Kostryukov; Natalia A. Lazareva; Yulia V. Moiseeva; Liya V. Tret’yakova; Alexey A. Kvichansky; Mikhail V. Onufriev; Victor A. Aniol; Margarita R. Novikova; et al. (Scientific Reports)
Abstract Aging is a complex process associated with multimorbidity. Hypertension, one of widespread states, is among main causes of age-related alterations in behavior, emotionality and sociability. We studied the effects of long-term isolated housing on anxiety, depressive-like and social behavior as well as changes in the adrenocortical and sympathetic systems in the aging normotensive Wistar Kyoto (WKY) and spontaneously hypertensive rats (SHR). Ten-month-old male rats of both strains were subjected to 90-day isolated or group housing. Surprisingly, social isolation induced only mild effect on anxiety without influencing other affective-related behaviors. No effects of isolated housing on sociability or social novelty preferences were revealed. Despite the adrenal gland hypertrophy in the SHRs, corticosterone levels remained stable within the period of isolation but the expression of nuclear glucocorticoid receptor (Nr3c1) mRNA in the adrenals was lower in the SHR as compared to WKY rats. Pre-existing hypertension, associated with SHR genotype, did not significantly contribute to the effects of social isolation. The data suggest that the aged WKY and SHR rats are relatively resilient to chronic social stress associated with isolated housing.